Argo Floats as a Novel Part of the Monitoring the Hydrography of the Bothnian Sea - Haavisto, Noora; Tuomi, Laura; Roiha, Petra; Siiriä, Simo-Matti; Alenius, Pekka; Purokoski, Tero (Frontiers in Marine Science, 2018)
We made an assessment of the hydrography in the Bothnian Sea based on data collected by the Argo floats during the first six years of operation in the Bothnian Sea (2012–2017). We evaluated the added value of Argo data related to the pre-existing monitoring data. The optimal usage and profiling frequency of Argo floats was also evaluated and the horizontal and vertical coverage of the profiles were assessed. For now we lose 4m of data from the surface due to sensor design and some meters from the bottom because of the low resolution of available bathymetry data that is used to avoid bottom collisions. Mean monthly temperature and salinity close to surface and below halocline from the float data were within the boundaries given in literature, although some variation was lost due to scarcity of winter profiles. The temporal coverage of the Argo data is much better than that of ship monitoring, but some spatial variability is lost since the floats are confined in the over 100m deep area of the Bothnian Sea. The possibility to adjust the float profiling frequency according to weather forecasts was successfully demonstrated and found a feasible way to get measurements from storms and other short term phenomena unreachable with research vessels. First six years of operation have shown that Argo floats can be successfully operated in the challenging conditions of the Bothnian Sea and they are shown to be an excellent addition to the monitoring network there. With multiple floats spread in the basin we can increase our general knowledge of the hydrographic conditions and occasionally get interesting data related to intrusions and mixing during high wind events and other synoptic scale events.